Mexican American religions: an introduction - Hendrickson, Brett (Religion in America, 2022)
"Mexican American Religions is a concise introduction to the religious life of Mexican American people in the United States. This accessible volume uses historical narrative to explore the complex religious experiences and practices that have shaped Mexican American life in North America. It addresses the religious impact of U.S. imperial expansion into formerly Mexican territory and examines how religion intertwines with Mexican and Mexican American migration into and within the United States. This book also delves into the particularities and challenges faced by Mexican American Catholics in the United States, the development and spread of Mexican American Protestantism and Pentecostalism, and a growing religious diversity. Topics covered include: Mesoamerican religions Iberian religion and colonial evangelization of New Spain The Colonial era Religion in the Mexican period The U.S.-Mexican War and the racialization of Mexican American religion Mexican migration and the Catholic Church Mexican American Protestants Mexican American Evangelical and Charismatic Christianity Mexican American Catholics in the 20th and 21st Centuries Curanderismo Religion and Mexican American Civil Rights Pilgrimage and borderland connections Mexican American Judaism, Islam, Mormonism, and Secularism Mexican American Religions provides an overview of this incredibly diverse community and its ongoing cultural contribution. Ideal for students and scholars approaching the topic for the first time, the book includes sections in each chapter that focus on Mexican American religion in practice"--